Factors Associated with Common Health Problems of the Ageing Population in a Rural Municipality: A Cross-sectional Study (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: With increase in life expectancy, gradual rise in number of aging populations is expected in near future. With multiple studies concerned either with younger or sick population, the age group of 40-60 years who are most likely to have change in social roles, exposure to risk factors and increased mental burden are neglected. The study identifies multiple of these health problems and factors associated with the age group and possible recommendations for the concerned authority.Methods and Materials:  A community based cross sectional study was conducted in Bhangaha Municipality of Mahottari district of Nepal with a sample size of 230 people in the age group of 40-60 years irrespective of gender. Face to face interview using a structured questionnaire was conducted with participant after informed verbal consent was received. The data collected were analyzed through SPSS ver.20. Association between socio-demographic structure and health problems were studied.Results:  Eye problem (52.6%) was the most common health problem of the participants followed by Gastrointestinal problems (36.1%) and Musculoskeletal problems (31.7%).  Significant association between age and eye problems was found but no such relationship was found between type of food and gastrointestinal problems. Type of family was strongly associated with irritability in the respondents.Conclusion: With exposure to multiple risk factors in the age group of 40-60 years, multiple health problems are encountered by the age group. Promotion of healthy practices and screening is the need for reduction of these issues.